DISCRIMINATION OF VARIETAL GROUPS AND HYBRIDS OF COFFEA CANEPHORA SPECIES USING MULTIVARIATE ANALYSIS - OLIVEIRA, Gabriela França; MIRANDA, Taiana Lopes Rangel; NASCIMENTO, Ana Carolina Campana; NASCIMENTO, Moysés; CAIXETA, Eveline Teixeira; SILVA, Letícia de Faria; ALKIMIM, Emilly Ruas; SILVA, Felipe Lopes da (Brazilian Journal of Biometrics, 2021)
Coffee growing is one of the most important agricultural activities in the world market. Among the commercially relevant species, there is Coffea canephora,which can be divided into the varietal groups Conilon and Robusta. These varietal groups have complementary agronomic interests. Because of this, hybrids are obtained through the crosses between these groups. Given the difficulty in differentiating between two varietal groups genotypes in the field, the correct discrimination is essential for the definition of crosses in breeding programs. In this context, the objective was to apply a discriminant analysis (DA) to define functions to differentiate between varietal groups and hybrids of canephora, as well as to identify the most relevant phenotypic traits in these functions. Data from 165 genotypes from the Instituto Capixaba de Pesquisa, Assistência Técnica e Extensão Rural e do Centro Agronómico Tropical de Investigación y Enseñanza were used for which different plant traits were measured. The quadratic DA applied was the one with the best performance for genotype discrimination, with an average apparent error rate of 0.0333. Cercosporiose incidence, rust incidence and vegetative vigor were the most important traits in the varietal groups’ discrimination.